2011
DOI: 10.1002/hep.24201
|View full text |Cite
|
Sign up to set email alerts
|

Complementary role of vitamin D deficiency and the interleukin-28B rs12979860 C/T polymorphism in predicting antiviral response in chronic hepatitis C

Abstract: The widely accepted interleukin-28B (IL-28B) rs12979860 C/T polymorphism and the more recently proposed vitamin D serum concentration are two novel predictors of the response to antiviral treatment in chronic hepatitis C virus (HCV) infection. This study aimed to verify whether the IL-28B rs12979860 C/T polymorphism and pretreatment serum vitamin D levels have independent or complementary roles in predicting the rates of sustained viral response (SVR). The present study included 211 consecutive, treatment-naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 32 publications
5
129
3
4
Order By: Relevance
“…Another noticeable difference between the studies is the prevalence of advanced fibrosis. In the 3 studies that reported no association of vitamin D with response [our current study, Kitson et al,2013, and Grammatikos et al,2011] prevalence of advanced fibrosis was 12%, 14% and 19%, while Bitetto et al [9] and Petta at al. [7] , who both found a relation between vitamin D levels and response, had patients with a high prevalence of advanced fibrosis (29% and 28%).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Another noticeable difference between the studies is the prevalence of advanced fibrosis. In the 3 studies that reported no association of vitamin D with response [our current study, Kitson et al,2013, and Grammatikos et al,2011] prevalence of advanced fibrosis was 12%, 14% and 19%, while Bitetto et al [9] and Petta at al. [7] , who both found a relation between vitamin D levels and response, had patients with a high prevalence of advanced fibrosis (29% and 28%).…”
Section: Discussioncontrasting
confidence: 40%
“…[6] A few studies have recently reported the association of serum vitamin D levels with fibrosis levels and response to treatment in genotypes 1,2,3 HCV. [7][8][9] Some other studies, however, have negated such evidence. [10] Two small trials have reported an improved SVR with vitamin D supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Italian cohort) were associated with a greater likelihood of HCV persistence, particularly in HCV GT1 and GT4 (Aparicio et al, 2010;Bitetto et al, 2011;Boglione et al, 2015;Boglione et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…[2][3][4] However, these studies were published by prestigious journals during consecutive years and provided independent and remarkable information, each of them including a different number of patients. Nevertheless, the significant association was lost if we reanalyzed it considering only one of these studies.…”
Section: Replymentioning
confidence: 99%
“…2 Caballeria states that the trial concluded that the efficacy of pentoxifylline is lower than that of prednisolone. However, the noninferiority endpoint of that study HEPATOLOGY, Vol.…”
Section: Is Pentoxifylline Still An Option In Severe Alcoholic Hepatimentioning
confidence: 99%